2021
DOI: 10.1021/jacs.0c11465
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modified Gold/Silver Superatoms as Artificial Elements at Nanoscale: Design Principles and Synthesis Challenges

Abstract: Pure and doped gold/silver clusters protected by monolayers of organic ligands have attracted much interest as novel functional materials owing to their nonbulk-like, size-specific properties. They can be viewed as chemically modified superatoms because their stabilities and properties are governed by the electron shell configurations of the Au/Ag cores. Chemically modified superatoms are unique from conventional atoms in that they have additional control parameters such as surface modification, compositions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
202
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(207 citation statements)
references
References 153 publications
3
202
2
Order By: Relevance
“…The findings obtained in this study are expected to provide clear design guidelines for the creation of highly functional heterogeneous catalysts using metal NCs, which have been reported thus far. [ 12 , 60 , 61 ]…”
Section: Discussionmentioning
confidence: 99%
“…The findings obtained in this study are expected to provide clear design guidelines for the creation of highly functional heterogeneous catalysts using metal NCs, which have been reported thus far. [ 12 , 60 , 61 ]…”
Section: Discussionmentioning
confidence: 99%
“…Four related LMO's oriented at about 124°from each other leading to a quasi tetrahedral arrangement are depicted, accounting for a set of four SP 3 -hybridized orbitals within the core. In addition, a set of five orbitals was obtained, accounting for the 1D 10 state. Within the current perspective based on the Au 22 4 + core, such a picture resembles the classical tetrahedral Ni(CO) 4 complex involving a sp 3 -hybridization of nickel 4s-and 4p-shells responsible for the stabilization of the CO-coordination, and the non-bonding 3d-Ni shells.…”
Section: Resultsmentioning
confidence: 99%
“…To date, significant achievements have been made toward the atomically precise metal nanoclusters in terms of synthesis, characterization and structure-reactivity relationship, and the relevant progresses can be summarized in recent reviews. [13][14][15][16][17][18][19][20][21][22][23][24][25] However, less summary and perspective have been made in the C 1 transformation catalyzed by metal nanoclusters. In this review, research processes of nanoclusters for C 1 conversion are highlighted, including thermal-driven reaction processes, such as CO Au 25 (SNap) 18 and Au 25 (PPh 3 ) 10 (PET) 5 X 2 and the large ligand steric hindrance of Au 25 (PPh 3 ) 10 (PET) 5 X 2 .…”
Section: Introductionmentioning
confidence: 99%
“…8a), implying that the coordinatively unsaturated (cus) gold atoms (Figure 8b) in the fresh Au 22 were active at low-temperature. DFT calculations revealed that the cus gold sites in the fresh Au 22 This article presented here has been accepted for publication in CCS Chemistry and is posted at the © 2021 Chinese Chemical Society.…”
Section: Introductionmentioning
confidence: 99%